The pricing of green bonds: are financial institutions special? - Serena Fatica; Roberto Panzica; Michela Rancan (Publications Office of the European Union, 2019)
The financial system plays a major role in the transition to a low-carbon economy. We investigate this issue analysing the recent developments and challenges in the bond and debt markets. First, we study the pricing of green bonds at issuance. We find a premium when green bonds are issued by supranational institutions and corporates while there is no effect for financial institutions. We also document an effect for external review and repeated access to this market. Second, we investigate lending decisions by banks issuing green bonds. Our results show that these lenders reduce their funding towards more polluting segments of the economy but limited to the amount of loans they granted as lead bank in the deal. This evidence may explain why we do not find a green premium for financial issuers. Yet it also suggests that the banking system may play a much larger role in channelling funds towards low-carbon activities, and thus reducing the environmental risks also for the financial system.
Keywords: G12; G20; Q52; Q53; Q54; 330; sustainable finance; climate change; bond interest rates; financial institutions